A pan-African spatial assessment of human conflicts with lions and elephants - Di Minin, Enrico; Slotow, Rob; Fink, Christoph; Bauer, Hans; Packer, Craig (Nature communications, 2021)
African lions ( Panthera leo ) and African savanna ( Loxodonta africana ) and forest ( L. cyclotis ) elephants pose threats to people, crops, and livestock, and are themselves threatened with extinction. Here, we map these human-wildlife conflicts across Africa. Eighty-two percent of sites containing lions and elephants are adjacent to areas with considerable human pressure. Areas at severe risk of conflict (defined as high densities of humans, crops, and cattle) comprise 9% of the perimeter of these species’ ranges and are found in 18 countries hosting, respectively, ~ 74% and 41% of African lion and elephant populations. Although a variety of alternative conflict-mitigation strategies could be deployed, we focus on assessing the potential of high-quality mitigation fences. Our spatial and economic assessments suggest that investments in the construction and maintenance of strategically located mitigation fences would be a cost-effective strategy to support local communities, protect people from dangerous wildlife, and prevent further declines in lion and elephant populations. Growing human population density and farming expansion are fuelling human-wildlife conflict. Here the authors map spatial conflict with lions and elephants across Africa, identify high-risk areas, and estimate the cost-effectiveness of mitigation fences.